Design And Build The Appropriate Technology Machinery For Shredded Fish Processing - Siswanto, Heru; Riyadi, Slamet; Siswadi, Siswadi; Setyono, Gatot; Khusna, Dwi; Nugroho, Wahyu (Journal of System Engineering and Technological Innovation, 2023)
The Shredded fish is produced by machines automatically, which can facilitate the production process. Previously the process was done conventionally in one production run. This problem prompted researchers to create a machine by combining three tool systems to become a shredded fish processing machine, including a system for separating meat and fish bones, a cooking furnace system, and a shredded dryer/spinner system that can be controlled electrically in the production process, in addition to the shredded produced more cleanly and efficiently in one production process. This machine utilizes the power of an electric motor of ¾ Hp, which is the driving force for the meat separator machine with a rotation speed of 2840 rpm and a production capacity of 30 Kg/hour.